PERANAN LOCUS OF CONTROL, SELF-SET DAN ORGANIZATIONAL-SET HURDLE RATES TERHADAP ESKALASI KOMITMEN PADA LEVEL PENGAMBILAN KEPUTUSAN PENGANGGARAN MODAL - ANDREAS BUDI SANTOSO (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Capital budgeting decision-making is an integral part of the success or failure of a manager. The decision was taken after a few calculations and consideration of alternatives. Escalation of commitment is the tendency of decision makers to proceed with the project that are not economical, although it has provided information on past poor performance and alternatives that may occur in the future. Managers tend to escalation of commitment in its decision making. In decision making is influenced by many things. The concept of locus of control is based on social learning theory, namely the extent to which a person feels the relationship of contingency between actions and their results. It is also influenced by the theory that man is a rational finite beings who have limited rational, so it found a lot of irrationality in the decision making process. A decision may be felt rational or irrational, and can be based on the assumption of weak or strong assumptions. Hurdle therefore used to reduce the rate of escalation of commitment made by a manager in determining the decisions to be taken.